A New Strategy for PI Tuning in Photovoltaic Irrigation Systems Based on Simulation of System Voltage Fluctuations Due to Passing Clouds - Guillén-Arenas, Francisco Jesús; Fernández-Ramos, José; Narvarte Fernández, Luis (MDPI, 2022)
One of the greatest challenges in stand-alone photovoltaic irrigation systems (PVIS) without batteries is the tuning of PID controllers and the evaluation of their performance once the system is tuned. Tuning method must be applied in clear days (constant irradiance) while performance must be evaluated in the most unfavourable circumstances, which occur when the passage of a cloud causes a sudden drop in available power. In short, tuning and testing must be done under different weather conditions. To solve this problem, a tuning method that is complemented by a method to simulate voltage fluctuations due to cloud passage has been developed. This allows tuning and evaluation of the system’s performance in the same session. Furthermore, the new PI tuning method achieves a better adjustment of the parameters and solves the instability problems that arise when applying traditional closed-loop tuning methods. Both methods use the feedforward input that most variable frequency drivers have. A signal generator is used to carry out the simulation of the clouds. This input is also used to introduce a triangular signal used for the tuning of the PI controller. The results show that the performance of the system, characterized by the voltage of the PV generator, with simulated clouds is similar to the response with real clouds. With regard to the tuning, the new method achieves better performance than previous methods. These methods can be applied on clear days, under conditions of constant irradiance, which greatly simplifies its implementation and greatly reduces the time required for commissioning the system.
Keywords: Sistemas de bombeo fotovoltaico; PV irrigation; PV system; PID tuning; Water pumping; Cloud simulation